237 IDENTIFYING PROVIDER AND PATIENT VIEWPOINTS IN DEVELOPING A DIABETES SELF-MANAGEMENT GUIDE. Issue 1 (1st January 2007) - Davis, K.; Bocchini, M. V.; Joyner, J.; Jain, S.; Wallace, A. S.; Seligman, H.; DeWalt, D.; Schillenger, D.; Arnold, C. L.; Davis, T. C.; Delgadillo, A.
Abstract : Background: Most current type 2 diabetes patient education materials are too complex for patients to understand and use. Objective: To solicit stakeholder input to develop a patient-centered guide to help patients effectively manage their diabetes. Methods: Sixteen focus groups followed by 63 cognitive interviews of patients and providers from private and public health settings in rural and urban communities in four states (LA, TX, CA, and NC) were conducted between 03/05 and 05/06. Focus groups were conducted using a structured moderator's guide that elicited feedback on current materials, barriers, and facilitators to patient management and suggestions for essential content. In addition, individual interviews elicited feedback on drafts of the guidebook and provided insight into comprehension, cultural appropriateness, and usefulness. Results: Focus group participants included 55 patients with diabetes, 85 physicians, 13 nurses, and 3 dietitians. Patients, identified by participating providers, were 62% female and 27% African American and ranged in age from 21 to 84. Physicians expressed a desire to teach patients yet were pessimistic about their ability to help patients make behavior changes. Physicians felt that patients needed to know the severity of diabetes, associated health risks, the meaning of hemoglobin A1C tests, and the importance of checking blood sugar regularly. Patients generally felt that current diabetes materials were overwhelming, covered too much information, and were written in an unappealing clinical tone. Many patients felt that they " knew more than they did ." Patients requested practical, everyday advice on how to live with diabetes. They particularly wanted practical strategies for such things as handling hunger, eating out, and safe ways to approach exercise. In fine-tuning the guidebook, individual patient interviews (67% female, 35% African American, 42% Latino, age range 35-73) revealed that patients preferred material that contained a conversational tone, suggestions from real people with diabetes, and photographs-not clip art-illustrating portion size and practical eating and exercise strategies. Conclusions: Patients and doctors differ in their views of the information needed in diabetes education material. A collaborative effort between patients and doctors to develop user-friendly material can yield more appealing and possibly more effective patient education.